1.3 DNA Methylation of Somatotropic Axis Genes in Relation to Postnatal Growth and Metabolism Following Ad.VEGF Treatment of Growth-Restricted Sheep Fetuses. (26th April 2013) - Carr, DJ; Aitken, RP; Milne, JS; Peebles, DM; Martin, JF; Zachary, IC; Wallace, JM; David, AL
Abstract : Introduction: We previously showed that adenovirus (Ad) mediated overexpression of vascular endothelial growth factor (VEGF) in the uteroplacental circulation increases fetal growth velocity in the overnourished adolescent sheep paradigm of fetal growth restriction 1 2 . Lambs born following Ad.VEGF therapy also demonstrated accelerated lean tissue accretion and enhanced insulin secretion following glucose challenge 3 . Herein we examined for putative epigenetic changes underlying these postnatal effects by quantification of methylation at cytosine:guanine (CpG) dinucleotides. Methods: DNA was extracted from liver samples obtained at 82 ± 0.2d postnatal age in 29 lambs born after prenatal treatment with Ad.VEGF (n = 16: 8 × Male/8 × Female) or Saline (n = 13: 7 × Male/6 × Female). After incubation with sodium bisulphite, PCR was performed using custom-designed primers targeting 9 CpG islands across 5 genes: insulin, growth hormone, insulin-like growth factor (IGF)1, IGF2 and H19. Using pyrosequencing, methylation status was determined by quantifying cystosine:thymine ratios at 35 individual CpG sites. Plasma IGF1/insulin levels were measured by RIA. Results: There were no significant differences in DNA methylation between Ad.VEGF and Saline groups, except at 1 of 4 CpG dinucleotides preceding IGF2 exon-6 (3.8 ± 0.59 vs. 1.9 ± 0.60%, p = 0.029). Irrespective of treatment, insulin gene methylation was greater in males than females (88.7 ± 0.23 vs. 87.0 ± 0.50%, p = 0.007) and negatively correlated with fasting insulin levels (r = –0.431, n = 28, p = 0.022). By contrast, IGF1 methylation tended to be lower in males than females (84.3 ± 0.16 vs. 84.8 ± 0.22%, p = 0.053) and was unrelated to plasma IGF1 levels. Conclusion: Increased postnatal growth rates in Ad.VEGF-treated lambs most likely reflect their relative size advantage at birth rather than altered epigenetic status of key somatotropic genes. References: Carr DJ, Aitken RP, Milne JS, et al . Maternal Ad.VEGF gene therapy increases fetal growth velocity in growth restricted sheep fetuses. BJOG 2011;118:1008-1009. Carr DJ, Aitken RP, Milne JS, et al . Prenatal gene therapy increases fetal growth velocity and alters uterine artery vascular reactivity in the absence of a measurable effect on uterine blood flow in a sheep model of fetal growth restriction. Archives of Disease in Childhood: Fetal and Neonatal Edition 2012;97(Suppl_1):A1. Carr DJ, Aitken RP, Milne JS, et al . Alterations in postnatal growth and metabolism following prenatal treatment of intrauterine growth restriction with Ad.VEGF gene therapy in the sheep. Archives of Disease in Childhood: Fetal and Neonatal Edition 2011;96(Suppl1):Fa7.